2014
DOI: 10.1088/0004-637x/786/2/93
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Systematic Error in Weak Lensing Cluster Surveys

Abstract: Weak lensing provides an important route toward collecting samples of clusters of galaxies selected by mass. Subtle systematic errors in image reduction can compromise the power of this technique. We use the B-mode signal to quantify this systematic error and to test methods for reducing this error. We show that two procedures are efficient in suppressing systematic error in the B-mode:(1) refinement of the mosaic CCD warping procedure to conform to absolute celestial coordinates and (2) truncation of the smoo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Such weak lensing mass maps provide an important means of studying the large-scale structure of the Universe as well as non-Gaussian features of the matter density field. For example, massive clusters of galaxies can be identified from peaks in mass maps (e.g., Miyazaki et al 2002Miyazaki et al , 2007Wittman et al 2006;Shan et al 2012;Utsumi et al 2014;Liu et al 2015). Correlations of mass maps with light maps constructed from galaxies and clusters of galaxies can reveal the connection between mass and light, by constraining mass-tolight ratios and galaxy biases (e.g., Hoekstra et al 2002;Okabe et al 2010;Jullo et al 2012;Chang et al 2016;Pujol et al 2016;Utsumi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such weak lensing mass maps provide an important means of studying the large-scale structure of the Universe as well as non-Gaussian features of the matter density field. For example, massive clusters of galaxies can be identified from peaks in mass maps (e.g., Miyazaki et al 2002Miyazaki et al , 2007Wittman et al 2006;Shan et al 2012;Utsumi et al 2014;Liu et al 2015). Correlations of mass maps with light maps constructed from galaxies and clusters of galaxies can reveal the connection between mass and light, by constraining mass-tolight ratios and galaxy biases (e.g., Hoekstra et al 2002;Okabe et al 2010;Jullo et al 2012;Chang et al 2016;Pujol et al 2016;Utsumi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tests of the projected matter distribution revealed by weak lensing against the distribution derived from the redshift survey show that the galaxies trace the three-dimensional large-scale matter distribution throughout the redshift range of the survey (Geller et al 2005). Later using both the DLS map and a field observed in better seeing with the Subaru telescope, Geller et al (2010), Kurtz et al (2012), and Utsumi et al (2014) demonstrate that thresholds for reliable detection of massive clusters of galaxies based on lensing maps have been overly optimistic. These results are consistent with the conclusions of larger surveys (e.g.…”
Section: The Hectospec Redshift Surveysmentioning
confidence: 97%
“…More recently, two weak lensing detections near this position have been reported. Utsumi et al (2014), in their analysis of a Subaru Suprime camera observation of a part of the DLS field F2, and Miyazaki et al (2015), in their weak lensing analysis of a Subaru Hyper Suprime-Cam (HSC) observation covering all of the same DLS field, both find weak lensing detections that are within ∼ 1 ′ (but on opposite sides) of the corresponding X-ray source position (of B11). A nearby optical cluster (z ∼ 0.54, Ascaso et al 2014) is found to be approximately ∼ 1.5 ′ away from the X-ray source and possibly consistent with the Miyazaki et al (2015) weak lensing peak.…”
Section: Source Detectionmentioning
confidence: 99%